2015
DOI: 10.1007/s40572-015-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

A New Era of Low-Dose Radiation Epidemiology

Abstract: The last decade has introduced a new era of epidemiologic studies of low-dose radiation facilitated by electronic record linkage and pooling of cohorts that allow for more direct and powerful assessments of cancer and other stochastic effects at doses below 100 mGy. Such studies have provided additional evidence regarding the risks of cancer, particularly leukemia, associated with lower-dose radiation exposures from medical, environmental, and occupational radiation sources, and have questioned the previous fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 84 publications
0
14
0
1
Order By: Relevance
“…However, there was few studies with strong evidence of hazard effect on human health. One of the reason is difficulties in identifying the true natural ionizing radiation risk, as comorbidities such as diabetes mellitus, cardiovascular disease, metabolic syndrome contribute negative effect to the whole organism as well [33]. Our findings seems to suggest that the first step in identifying clear effect on health due to natural radiation is conducting a good epidemiological study in order to detect an annual effective dose of radiation.…”
mentioning
confidence: 83%
“…However, there was few studies with strong evidence of hazard effect on human health. One of the reason is difficulties in identifying the true natural ionizing radiation risk, as comorbidities such as diabetes mellitus, cardiovascular disease, metabolic syndrome contribute negative effect to the whole organism as well [33]. Our findings seems to suggest that the first step in identifying clear effect on health due to natural radiation is conducting a good epidemiological study in order to detect an annual effective dose of radiation.…”
mentioning
confidence: 83%
“…In the 1980s, the predominant source of radiation exposure (>80%) was from natural background radiation in the USA. By the mid 2000s, the estimated per capita annual dose almost doubled from 3.6 mSv to 6.2 mSv, mainly due to higher medical radiation exposure, in particular from diagnostic procedures such as CT scans or X-rays (summarized by Kitahara et al 2015). A number of studies found elevated cancer risks (in particular leukemia and brain tumors) after multiple CT scans in children and adolescents (e.g.…”
Section: Susceptibilitymentioning
confidence: 99%
“…Powerful new epidemiological studies over the past decade have provided estimates both more accurate and demonstrating greater radiation-related health risks than previously estimated (Kitahara et al 2015). These studies are made possible by electronically linking data on radiation exposure, especially at low doses, and health outcomes for large numbers of people, such as for children who underwent a CT scan funded by national health insurance, who subsequently developed a cancer reported to their local cancer registry.…”
Section: Stigma and Discriminationmentioning
confidence: 99%